Disease tolerance: a protective mechanism of lung infections - Xu, Jianqiao; Xiao, Nan; Zhou, Dongsheng; Xie, Lixin (Frontiers in Cellular and Infection Microbiology, 2023)
Resistance and tolerance are two important strategies employed by the host immune response to defend against pathogens. Multidrug-resistant bacteria affect the resistance mechanisms involved in pathogen clearance. Disease tolerance, defined as the ability to reduce the negative impact of infection on the host, might be a new research direction for the treatment of infections. The lungs are highly susceptible to infections and thus are important for understanding host tolerance and its precise mechanisms. This review focuses on the factors that induce lung disease tolerance, cell and molecular mechanisms involved in tissue damage control, and the relationship between disease tolerance and sepsis immunoparalysis. Understanding the exact mechanism of lung disease tolerance could allow better assessment of the immune status of patients and provide new ideas for the treatment of infections.